Redefining the Public as a Thing in the Care Governance Paradigm - Ahyar, Muhammad Ahnaf Nadewa Biyangsa; Niswaty, Risma; Baharuddin, Aris; H, Herman (Program Pascasarjana Universitas Negeri Makassar, 2024)
This study examines the redefinition of the public as things in the care governance paradigm. Care governance is an alternative paradigm that can be used to respond to the crisis that occurred in the anthropocene era. The anthropocene era is an era in which human activities have a dominant influence on changes in ecosystems and the order of life on earth, even exceeding the power of nature itself. This era is also marked by rapid and massive changes in the earth's system. This condition demands a change in the way of viewing the public and its relationship with things. This study uses a literature study method by reviewing various relevant sources, such as scientific journals, books, and other publications that discuss the anthropocene, care governance, and the redefinition of the public. The analysis was carried out using an exploratory qualitative approach to deeply understand the concept of the public as things in the context of care governance. The results of the study show that in the care governance paradigm, the public is no longer understood anthropocentrically as a separate and superior entity, but rather as an integral part of the network of life that is interrelated and dependent on things or non-humans. This redefinition requires a collective responsibility to care for and maintain the sustainability of things as part of the sustainability of the public itself